2014
DOI: 10.1016/j.transproceed.2014.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus, Cyclosporine, and Thrombotic Microangiopathy: Clinical Role and Preventive Tools in Renal Transplantation

Abstract: Results confirm the pivotal role of IS drugs in the onset of de novo TMA. On the basis of literature, we could speculate a sequence of endothelial damage by CNI, on which everolimus fits hindering the repair of endothelial injury. Therefore, high blood levels of CNI and mTORi seem to predispose patients to posttransplant TMA. Combined monitoring of these 2 drugs might be used to prevent the complication. Σ [everolimus TLC + (cyclosporine C2/100)]>12.5 ng/mL should be avoided as a surrogate risk factor for adve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
1
20
0
1
Order By: Relevance
“…antigen) antibodies may be associated to microvascular inflammation, early acute rejection and allograft loss as previously reported. [27][28][29] TMA associated only to drug toxicity was relatively infrequent in our findings, compared to what was observed by Nava et al [30]. On the other hand, in accordance with what was recently published by Bayer et al [31], the usual presence of multiples conditions causing or precipitating TMA supports the "multiple hit hypothesis" [8,32] that speculates that TMA is the consequence of the combination of genetic predisposition and several trigger factors/conditions in both native and transplanted kidneys.…”
Section: Timelinesupporting
confidence: 92%
“…antigen) antibodies may be associated to microvascular inflammation, early acute rejection and allograft loss as previously reported. [27][28][29] TMA associated only to drug toxicity was relatively infrequent in our findings, compared to what was observed by Nava et al [30]. On the other hand, in accordance with what was recently published by Bayer et al [31], the usual presence of multiples conditions causing or precipitating TMA supports the "multiple hit hypothesis" [8,32] that speculates that TMA is the consequence of the combination of genetic predisposition and several trigger factors/conditions in both native and transplanted kidneys.…”
Section: Timelinesupporting
confidence: 92%
“…cancer) has forced the need to find a balance between rigorous immunosuppression and adverse drug side effects. Effective modern immunosuppression requires blockade of one or more of the three stages in the life-cycle of lymphocytes to aid in increasing graft half-life by suppressing graft rejection [38] . The site of action defines the immunosuppressive therapy such as lymphocyte depletion, lymphocyte diversion, and lymphocyte-activation blockade.…”
Section: Immunosuppressive Strategies In Current Practicementioning
confidence: 99%
“…These effects are proven to be implicated in TMA pathogenesis[ 15 , 16 ]; (2) The VEGF inhibition has been recently proven to be associated with reduced renal levels of complement factor H (CFH)[ 17 ]. Patients with underlying CFH genetic mutations are more susceptible to develop de novo TMA, particularly with mTORi exposure[ 7 ]; (3) Repair of endothelial injury could be hampered by mTORi use[ 18 - 20 ]; and (4) Furthermore, the procoagulant and the antifibrinolytic activity of mTORi might play additional roles in de novo TMA development[ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of development of TMA with combined CNI and mTORi protocols is higher than using mTORi alone, an effect that has been documented in several studies. While Fortin et al[ 18 ] reported that the highest risk of de novo TMA was in the group using CNI and mTORi, Nava et al[ 20 ] studied 396 KTR, 36 (7.3%) developed TMA and 17 of them were drug-related. Not only were the drug levels of CNI and mTORi higher in the TMA group, but the sum of both drug levels in the TMA group was also higher[ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%